Exploring feedback mechanisms for nitrogen and organic carbon cycling in tropical coastal zones - Jiang, Shan; Jin, Laiqun; Jin, Jie; Ibánhez, Juan Severino Pino; Wu, Ying; Zhang, Jing (Frontiers in Marine Science, 2022)
The anthropogenic introduction of significant amounts of reactive nitrogen in the coastal zone particularly since the discovery and application of the Haber-Bosch process has profound consequences over organic carbon storage and transformations at both regional and global scales. Here, we review our current knowledge on cause-effect chains for nitrogen, especially dissolved inorganic nitrogen, on organic carbon cycling in coastal tropical systems. We focus on the feedback mechanisms for turnover of different organic carbon species to nitrogen excess and links to current environmental and climate changes. We pay special attention to organic carbon dynamics in tropical coasts due to their high primary productivity, rapid sedimentation, and significant needs of nitrogen for agriculture and industry usages. Together with land-use changes and economy development, we highlight the vulnerability of carbon storage in tropical coasts triggered by nitrogen overloading and outline possible industrial strategies with low carbon cycling disturbance to benefit the development of tropical countries.